2021
DOI: 10.1101/2021.03.19.21253806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CNVxplorer: a web tool to assist clinical interpretation of CNVs in rare disease patients

Abstract: Copy Number Variants (CNVs) are an important cause of rare diseases. Array-based Comparative Genomic Hybridization tests yield a ~12% diagnostic rate, with ~8% of patients presenting CNVs of unknown significance. CNVs interpretation is particularly challenging on genomic regions outside of those overlapping with previously reported structural variants or disease-associated genes. Recent studies showed that a more comprehensive evaluation of CNV features, leveraging both coding and non-coding impacts can signif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 73 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Second, it is important to assess the consistency of the patient's phenotype with the targeted genomic elements, as this can help prevent the misclassification as pathogenic of CNVs affecting Mendelian genes not associated with the clinical signs investigated. Indeed, this aspect has already been incorporated into current computational frameworks to assist the manual assessment of CNVs [3,13]; it would require the systematic incorporation of phenotypes into reference databases, such as Clinvar. Third, there is also a need for large-scale mutational scanning projects on cellular systems [14], to provide experimental evidence for CNVs not affecting coding genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, it is important to assess the consistency of the patient's phenotype with the targeted genomic elements, as this can help prevent the misclassification as pathogenic of CNVs affecting Mendelian genes not associated with the clinical signs investigated. Indeed, this aspect has already been incorporated into current computational frameworks to assist the manual assessment of CNVs [3,13]; it would require the systematic incorporation of phenotypes into reference databases, such as Clinvar. Third, there is also a need for large-scale mutational scanning projects on cellular systems [14], to provide experimental evidence for CNVs not affecting coding genes.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate the use of CNVscore, we have implemented an application programming interface (API) supporting remote queries. In addition, CNVscore is integrated into the CNVxplorer framework for the clinical assessment of CNVs identified in patients with rare diseases (http://cnvxplorer.com, [3]). The complete list of CNVs identified in a patient's genome can, therefore, first be filtered by combining the pathogenicity and uncertainty CNVscores, to obtain a shortlist of highconfidence candidate pathogenic CNVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DisGeNET ( http://www.disgenet.org/web/DisGeNET/menu ) 88 , VarElect ( http://varelect.genecards.org/ ), and Schizophrenia Exome Sequencing Genebook 89 , 90 were also used to characterize variations. DECIPHER (DatabasE of genomiC varIation and Phenotype in Humans using Ensembl Resources; https://www.deciphergenomics.org ) 91 and CNVxplorer ( http://cnvxplorer.com ) 92 were used to study the pathogenicity and conservation of the identified CNVs. All genomic data for molecular variants in this study were compatible with Genome build GRCh37.…”
Section: Methodsmentioning
confidence: 99%
“…One reason for this is the sheer volume of variational possibilities in genomic data. For example, it has been shown that CNVs are associated with several rare diseases (Li et al ., 2020), but such analyses either use simple statistics or require visual inspection of CNV distributions (Requena et al ., 2021; Collins et al ., 2020; MacDonald et al ., 2014). Since there are many types of CNVs and SVs (deletions, inversions, tandem duplications, translocations), manual development of machine learning features requires time-consuming, error-prone, experts’ labor.…”
Section: Introductionmentioning
confidence: 99%